The perceptions and attitudes of form four malay students towards their peers speaking english - Hazman, bin Murshidi (University Malaysia Sarawak, UNIMAS., 2005)
This study seeks to find out Form Four Malay students' attitudes and perceptions oftheir peers speaking English. The samples for this study were twenty Form Four Malay students from one urban secondary school in the Kuching-Samarahan division. The data were obtained through open ended interview. Data from the open ended interview were analysed descriptively. The findings of the study indicated that the Form Four Malay students have positive attitudes and perceptions towards their peers speaking English.